Integrated Herd-Health Package: Optimizing Small Ruminants' Health in Tunisia's AE Transect El Kef-Siliana – An Integrated Package Guideline - Tebourbi, Ons; Mannai, Amal; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2023)
The integrated herd health package guideline involves various aspects such as animal nutrition, disease prevention (vaccination, biosecurity measures, etc.), general flock management and animal welfare. By addressing these aspects, the guideline provides guidance and recommendations, ultimately ensuring the overall health, productivity, profitability, and welfare of the herds. Additionally, it contributes to farms’ sustainability.